Measurement of MMP-9 and -12 degraded elastin (ELM) provides unique information on lung tissue degradation - Skjøt-Arkil, Helene (BioMed Central, 2012)
BACKGROUND: Elastin is an essential component of selected connective tissues that provides a unique physiological elasticity. Elastin may be considered a signature protein of lungs where matrix metalloprotease (MMP) -9-and -12, may be considered the signature proteases of the macrophages, which in part are responsible for tissue damage during disease progression. Thus, we hypothesized that a MMP-9/-12 generated fragment of elastin may be a relevant biochemical maker for lung diseases. METHODS: Elastin fragments were identified by mass-spectrometry and one sequence, generated by MMP-9 and -12 (ELN-441), was selected for monoclonal antibody generation and used in the development of an ELISA. Soluble and insoluble elastin from lung was cleaved in vitro and the time-dependent release of fragments was assessed in the ELN-441 assay. The release of ELN-441 in human serum from patients with chronic obstructive pulmonary disease (COPD) (n = 10) and idiopathic pulmonary fibrosis (IPF) (n = 29) were compared to healthy matched controls (n = 11). RESULTS: The sequence ELN-441 was exclusively generated by MMP-9 and -12 and was time-dependently released from soluble lung elastin. ELN-441 levels were 287% higher in patients diagnosed with COPD (p < 0.001) and 124% higher in IPF patients (p < 0.0001) compared with controls. ELN-441 had better diagnostic value in COPD patients (AUC 97%, p = 0.001) than in IPF patients (AUC 90%, p = 0.0001). The odds ratios for differentiating controls from COPD or IPF were 24 [2.06–280] for COPD and 50 [2.64–934] for IPF. CONCLUSIONS: MMP-9 and -12 time-dependently released the ELN-441 epitope from elastin. This fragment was elevated in serum from patients with the lung diseases IPF and COPD, however these data needs to be validated in larger clinical settings.